Det skapades delaktighet i det sköna - En studie av Dionysios Areopagitens syn på det skapades delaktighet i det sköna enligt forskarna Brandon Thomas Sammon och Filip Ivanovic - Sacredeus,John (2021)
The aim of this thesis is to investigate the theology of beauty in the teachings of Dionysius Areopagita through the works of the researchers Brandon Thomas Sammon and Filip Ivanovic. More specifically the thesis asks the question how Dionysius, according to Sammon and Ivanovic, describes that created creatures can participate in beauty. The study of Dionysius has in the last decades seen a renaissance. The aspect of beauty in Dionysius thought has, until Sammon and Ivanovic published their works, been largely neglected. In their research of Dionysius, Sammon and Ivanovic stand in the research paradigm that came with Hans Urs von Balthasar and Andrew Louth - which states that Dionysius is a Christian with neoplatonic language and influence. The thesis starts with an examination how Sammon and Ivanovic, as well as the research paradigm they are apart of, approach Dionysius and his texts. How they see the pseudonym of the author as a key to understand the texts, that the texts are meant to aspire worship to God and how Dionysius unite his Christian and neoplatonic heritage. The thesis then examines how this research paradigm view the specific texts that are important for the understanding of Dionysius theology of beauty, namely Mystical Theology, The Divine Names, The Celestial Hierarchy and The Ecclesiastical Hierarchy. The thesis then moves to the main chapter where the works of Sammons and Ivanovics on the theology of beauty in Dionysius are investigated. This investigation is divided into three sections: how the name beauty applies to God and Creation, how God and Creation relates to each other through the movements of beauty and lastly the role of hierarchy for participation in beauty. The results of this investigation are analysed through a cross-fertilization aiming to deepen the understanding of the theology of beauty in Dionysius and stimulate further research. The created creatures participate with the transcendent beauty’s movements, which is a secondary participation and not a primary participation in God himself. Creation is apart of a circular movement where everything exists (monos), proceeds (próodos) and returns (epistrophê) to the transcendent beauty. There is also what Sammon calls a ”cruciform movement”, that when the created creatures participate in the beauty of God vertically, they participate with each other horizontally. These movements of the transcendent beauty Ivanovic sees as a result of God’s love (eros) for Creation and takes place in the hierarchy. It is in the hierarchy that the created creatures can participate with these movements of the transcendent beauty and with other creatures, which Ivanovic names as deification.
Keywords: Key words: Beauty; participation; Dionysius; Sammon; Ivanovic; hierarchy; deification; neoplatonism Mystical Theology; The Divine Names; The Celestial Hierarchy; The Ecclesiastical Hierarchy.